COMMUNITY LANGUAGE LEARNING (CLL): Empowering Speaking Skill at SMP Bina Mitra Wahana Pekanbaru - Dahler Dahler (Universitas Lancang Kuning, 2015)
The purpose of this research is to identify the effect of using Community Language Learning (CLL) Methodtowards speaking skill. This experimental design uses 48 students from class VII of SMP Bina Mitra Wahana Pekanbaru. The VIIA sets as the experiment class and VIIB set as the control class. Instrument in this research was oral test. The data were analyzed using t-test. The result of the test showed that the average score of students’ pre test was 68,50 and then the average of students post test was 74,58. The results of this research found that the alternative hypothesis was accepted and rejected a hypothesis null. It can be seen from the t-test (0.000) significant at the level of 0.05. The result of N-Gain of experimental class was 0,31. It means that the significant of strategy that used in experimental class was Middle because the average of N-Gain was 0.31. From the above explanation, the researchers concluded that Community Language Learning (CLL) Method effective for teaching speaking skill.